STUDI FENOMENOLOGI KONTRUKSI DAN AKOMODASI PPAI KETAPANG TERHADAP BUDAYA MASYARAKAT - Sutomo, Sutomo (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2020)
This study aims to reveal and understand something behind a little-known social phenomenon. The expected advantage of using qualitative research methods is to provide complex details about phenomena that are difficult to express by quantitative methods. Important concepts of public understanding about; Knowledge, attitudes and actions will be more easily revealed with this method. The process of social construction, the core of pesantren establishment is in order to realize the human society and pious people to Allah SWT, for the realization of the ideals of the Indonesian nation into Baldatun Thoiyibatun Warabbun Ghofur or â€œgemah ripah loh jinawe toto tentrem kerto raharjoâ€. Approach in order to menyantrikan surrounding communities, then made activities that accommodate the needs and culture of society. The reality of cultural accommodation made by PPAI Ketapang is poured in various activities which include: First, art culture, Both system of knowledge and skill. The third is the organizational system. Fourth, is the livelihood system. Fifth, the system of technology and the sixth, is the religious system.Keywords: pesantren; social construction; cultural accommodation